STUDI TINGKAT BAHAYA LONGSOR PADA AREAL PENAMBANGAN BATU DI DESA BUKIT PULAI KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Novita, Nevi - (STKIP PGRI Sumbar, 2014)
The objectives of this study are to identify and analyze the land characteristics on the stone mining areas at the Bukit Pulai Village, Sub-district of Batang Kapas, Pesisir Selatan District. The type of this research is quantitative descriptive that leads to disclosure of the facts and analysis needed. The sample selection of this study using purposive sampling method so that be obtained 3 locations in the study area that not be mined, already be mined, and being be mined. those three samples were analyzed in the soil laboratory for soil texture, soil permeability and soil bulk density. The data of field observations and the results of laboratory explained that land characteristics of the three samples for the solum depth denote O horizon, A and B from shallowest â depth with a range 27 - 91 cm, for the soil texture, including clay soil , dusty clay soil, with soil structure including solid soil, crusts soil for Bulk Density with ranged 1.11 - 1.18 g/cm3, with permeability ranged 0.57 - 1.29 cm/hour. For the tilt ranged 25 - 45%, with a slope length ranged 50 - 255m, and the shape of the slope are straight, concave, complex, with the height of the relief 2400 - 2600 m and for the location that not be mined the springs can not be found, for the location that already be mined there be found 2 springs and for the location that being be mined there be found seepage paths, with the land utilization for mixed farms, bush, and the averages of annual rainfall 2316,8 mm/year. Based on research of that three samples obtained the moderate level of landslide risk that be found in the location that not be mined, the high level of landslide risk that be found in the location that already be mined, and the very high level of landslide risk that be found in the location that being be mined.